2021
DOI: 10.1186/s12955-021-01846-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between occupational factors, depression, and health-related quality of life in military women in the Republic of Korea: a cross-sectional study

Abstract: Background Health-related quality of life (HRQOL) is an important concept to consider both individuals' ability to manage their daily lives and health status across the lifespan. Despite this variable's importance, there is a lack of clarification on the factors associated with HRQOL, especially for military women. The aim of this study was to examine factors associated with HRQOL of military women in the Republic of Korea (ROK) Army. Methods This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The result found in this study showed a prevalence of 34% of women with signs/symptoms of depression. In addition, studies have shown a prevalence of signs/symptoms of 3.5% of postmenopausal women <60 years (Park & Kim, 2018b), 35.3% employed, compared to unemployed, (Baskan et al, 2016, and 45.9% of military women (Kwon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result found in this study showed a prevalence of 34% of women with signs/symptoms of depression. In addition, studies have shown a prevalence of signs/symptoms of 3.5% of postmenopausal women <60 years (Park & Kim, 2018b), 35.3% employed, compared to unemployed, (Baskan et al, 2016, and 45.9% of military women (Kwon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The position they hold within their work influences their QoL, as shown in a study carried out with military women, in which all of them had scores in the domains of poor mental aspects, but the officers, whose position requires more responsibility, were worse off compared to the non-commissioned officers. since demand and stress are greater (Kwon et al, 2021).…”
Section: Discussionmentioning
confidence: 99%